O papel do estagiário nas organizações públicas brasileiras: um estudo de caso no Tribunal de Contas do Estado do Amazonas - Noronha, Nayrone Ruiz (Brasil, 2024)
The present study aimed to analyze the role of the trainee in the Court of Accounts of the State of Amazonas and the reasons why the body has a quantitative high number of interns. The methodology used was exploratory and descriptive, qualitative approach and case study as a method. The data were collected through documentary analysis and structured interviews and analyzed using the Content Analysis method. The results showed that the intern at TCE AM plays a role in supporting the server in low-cost activities and medium complexity, whose selection and recruitment process takes place annually, always aligned with the needs of the organization. It was found that possible reasons for the large number of interns at the agency include a high demand for work and the insufficient number of servers. Furthermore, interns are considered an economical workforce compared to civil servants at the beginning of their careers elementary and secondary levels. Possible positive consequences include the realization of work, filling the shortage of servers and the good performance of activities by interns. As possible negative reflections of this high quantitative are high turnover, time spent on training and loss of administrative memory.